1985
DOI: 10.1111/j.1348-0421.1985.tb00897.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Antigenic Structure of Japanese Encephalitis Virus Using Monoclonal Antibodies

Abstract: The antigenic relationships among 11 strains of Japanese encephalitis ( JE) virus were analyzed by using monoclonal antibodies (NARMA) against the Nakayama-RFVL strain in hemagglutination-inhibition (HI) and neutralization (Nt) tests. Of the 14 JE virus-specific HI antibodies, all except NARMA 5 showed Nt reactivity with the homologous strain. The HI and Nt titers of these antibodies were not parallel. The 14 antibodies included the following characteristic antibodies : NARMA 3 is a species-specific antibody w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…The amino acid differences between the vaccine strains and the GI strains did not exceed 2.4 %, indicating that the difference may not influence the efficacy of the vaccines. Previous studies have identified individual residues within the E protein that are related to the recognition of JEV by neutralizing antibodies (Crill & Chang, 2004;Goncalvez et al, 2008;Kobayashi et al, 1985;Morita et al, 2001;Vogt et al, 2009;Wu et al, 2003). Although the sequence variation between the vaccine strains and GV strains do not correspond to epitope residues, only a limited number of residues could be responsible for the decreased neutralization ability of the vaccines against GV strains.…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid differences between the vaccine strains and the GI strains did not exceed 2.4 %, indicating that the difference may not influence the efficacy of the vaccines. Previous studies have identified individual residues within the E protein that are related to the recognition of JEV by neutralizing antibodies (Crill & Chang, 2004;Goncalvez et al, 2008;Kobayashi et al, 1985;Morita et al, 2001;Vogt et al, 2009;Wu et al, 2003). Although the sequence variation between the vaccine strains and GV strains do not correspond to epitope residues, only a limited number of residues could be responsible for the decreased neutralization ability of the vaccines against GV strains.…”
Section: Discussionmentioning
confidence: 99%
“…The JE virus Kamiyama strain (15), which was isolated from human brain in Fukuoka (Japan) in 1966, was used in this study. The virus was propagated in C6/36 cells (9) as described previously (15) Virus titration and determination of number of infected cells. The virus titer was assayed by plaque formation on Vero cells by the method of Kimura-Kuroda and Yasui (12) .…”
Section: Methodsmentioning
confidence: 99%
“…The number of infected monocytes was determined by immunoperoxidase staining using horseradish peroxidase (HRPO)-labeled F(ab')2 fragment of NARMA 7 (JE species-specific monoclonal antibody) (14) at 48 hr after infection as described previously (15) . The infected monocytes were air-dried on glass slides and fixed with acetone at -20 C for 10 min, and reacted with HRPO-F (ab') 2 fragment of NARMA 7 at 37 C for 1 hr.…”
Section: Methodsmentioning
confidence: 99%
“…The amino acid change at E51 would change the conformation of the E protein in this region. The 10-fold haemagglutination inhibition activity difference of Narma3 between strains Nakayama and Kamiyama may result from their amino acid difference at E-51 (Kobayashi et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Antigenic, biochemical and genetic differences between JE virus strains isolated from different areas have been observed by cross-neutralization (Banerjee, 1975), oligonucleotide fingerprinting (Banerjee & Ranadive, 1984;Hori, 1986), monoclonal and polyclonal antibody reactivities (Kobayashi et al, 1984(Kobayashi et al, , 1985Wills et al, 1992) and by limited (240 bp) genomic sequence comparison (Chen et al, 1990(Chen et al, , 1992Huong et al, 1993). Chen et al (1990Chen et al ( , 1992 suggested that JE viruses could be divided into four genotypes using 12% nucteotide divergence as a cut-off point for virus relationships when comparing prM gene segments.…”
Section: Introductionmentioning
confidence: 99%